Development of coating for formaldehyde scavengers in wood composite - Jeevan Nair, Vasudevan (2015)
Wood composite is also known as wood engineering. This field is available due to its ability to overcome the current limitation faced by applying natural lumber wood. The many advantage that wood-composite have over natural lumber makes it more desirable in long-term usage. In the production of wood-composite, the agent use to bind wood together is urea formaldehyde. The issue faced when urea formaldehyde is used, that it will produce free formaldehyde which is rather cancerous to human beings. Hence, steps have to be taken to reduce the emission of urea formaldehyde. The step proposed in this research is utilizing formaldehyde scavengers. But if scavengers are applied directly during the production of wood composite, it will affect the credibility of the product and also react will the urea formaldehyde. Thus, a study on developing a typical wax or polymer coating for these scavengers could solve the problem. Once, the coating is developed, it is incorporated to the preparation of the medium density fibreboard and after that, tests are conducted to characterize its properties. To study the feasibility of success of this research, the parameter studied is mechanical properties of the wood and the formaldehyde emission of the finished product. The focus of mechanical properties is the internal bonding, modulus of elasticity and modulus of rupture to determine effect of scavengers to the wood panel. In formaldehyde emission, perforator and desiccator methods are applied to determine the concentration of formaldehyde liberated. From the proposed scavengers used, sodium metabisulfite and ammonium bisulfite, sodium metabisulfite shows great effectivity in reducing the formaldehyde liberation followed by ammonium bisulfite. However, ammonium bisulfite affected the mechanical properties of the board greatly, where else, sodium metabisulfite did not affect adversely. With this study, it could provide the wood- composite industry an alternative to open new market with this method of producing wood-composite products.